Digitalisasi Prosodi dalam Syair Gulung Ketapang: Kajian Fonetik Akustik - Oktaviani, Yolanda; Sulissusiawan, Ahadi; Patriantoro, Patriantoro (Jurnal Bahastra, 2025)
This study examines the digitalization of prosody in Syair Gulung Ketapang as an intersection of linguistics and literature, particularly within the domain of verse studies. The research addresses the problems related to the digitalization of prosodic features, including duration, intensity, frequency, and the generation of Praat images, as well as their pedagogical implications in Indonesian language learning. Employing a descriptive qualitative approach, data were collected through documentation techniques using recording devices, mobile phones, and computers. The primary data source was the oral performance of Syair Gulung Ketapang delivered by the poet Mursalin, consisting of phrases, clauses, and sentences. The digitization process was conducted using the Praat software, which produced measurable values of duration, intensity, frequency, and visual representations of prosody. The analysis revealed eight average duration values per line, eight duration values per stanza, eight average intensity values, eight average frequency values, and twenty-four Praat images, which were further developed into one teaching material product. The findings demonstrate that prosodic digitalization not only enriches literary and linguistic analysis but also provides practical contributions to language learning, particularly by integrating technology into the study of oral traditions.